2022
DOI: 10.1210/endocr/bqab269
|View full text |Cite
|
Sign up to set email alerts
|

Human INHBB Gene Variant (c.1079T>C:p.Met360Thr) Alters Testis Germ Cell Content, but Does Not Impact Fertility in Mice

Abstract: Testicular derived inhibin B (α/βB dimers) acts in an endocrine manner to suppress pituitary production of follicle stimulating hormone (FSH), by blocking the actions of activins (βA/B/βA/B dimers). Previously, we identified a homozygous genetic variant (c.1079T>C:p.Met360Thr) arising from uniparental disomy of chromosome 2 in the INHBB gene (βB-subunit of inhibin B and activin B) in a man suffering from infertility (azoospermia). In this study, we aimed to test the causality of the p.Met360Thr variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For age series data, a t-test was used to compare genotypes at each age point. Significance of apoptosis data was assessed using a script in RStudio as previously described (47).…”
Section: Discussionmentioning
confidence: 99%
“…For age series data, a t-test was used to compare genotypes at each age point. Significance of apoptosis data was assessed using a script in RStudio as previously described (47).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the mouse suggests that activin A plays a dominant role in testis function relative to activin B and inhibin B, as β B -subunit null mice have normal testes and fertility (Vassalli et al 1994). However, in men, maintenance of β B -subunit production is important for normal testis function (Meachem et al 2001, Houston et al 2022.…”
Section: Roles Of Activins and Inhibins In Reproductive Physiologymentioning
confidence: 99%
“…Human genetic and diagnostic studies corroborate the findings in mice highlighting the importance of inhibins and activins in the maintenance of reproductive health. It has been demonstrated that variations in the INHA, INHBA and INHBB genes are associated with premature ovarian failure (Harris et al 2005, Chand et al 2007), ovarian cancer (Tournier et al 2014) and male infertility (Li et al 2015, Houston et al 2022. Only recently, two discrete INHBB gene variations were identified in infertile men (Houston et al 2022).…”
Section: In Humans Alterations To Inhibins and Activins Are Also Asso...mentioning
confidence: 99%
See 2 more Smart Citations